2019
DOI: 10.1016/j.heliyon.2019.e01747
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of angiotensin -1 converting enzyme inhibition and antioxidative properties of Azadirachta indica seed protein hydrolysates

Abstract: Neem ( Azadirachta indica ) seed protein hydrolysates were investigated for in vitro antioxidant and angiotensin 1-converting enzyme (ACE)-inhibitory activities. Neem seed proteins were hydrolysed using pepsin, trypsin and Alcalase. The degree of pepsin hydrolysis of neem seed protein was significantly higher (p < 0.05) than those of trypsin and Alcalase hydrolysis. Proteolytic hydrolysis of the isolate resulted in hydrolysates with improved Arg/Lys ratio, with pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The IC 50 of hydrolysate was determined using different concentrations to give a value of 70.0 ± 4 µg/mL, as shown in Figure 1 . Based on the concentration of hydrolysate samples, similar results reported that the ACE inhibitory activity of neem ( Azadirachta indica) seeds peptides was evidently increased with an increase in concentration of the peptide hydrolysate [ 24 ]. Similarly, studies reported that a triple-juice combination (pear, hemp seeds, and pumpkin seeds) exhibited higher ACE inhibition activity (IC 50 of 82.54 µg/mL) than single (IC 50 of 731.15 µg/mL) or double-juice combinations (IC 50 of 245.72 and 117.67 µg/mL) [ 25 ].…”
Section: Resultsmentioning
confidence: 85%
“…The IC 50 of hydrolysate was determined using different concentrations to give a value of 70.0 ± 4 µg/mL, as shown in Figure 1 . Based on the concentration of hydrolysate samples, similar results reported that the ACE inhibitory activity of neem ( Azadirachta indica) seeds peptides was evidently increased with an increase in concentration of the peptide hydrolysate [ 24 ]. Similarly, studies reported that a triple-juice combination (pear, hemp seeds, and pumpkin seeds) exhibited higher ACE inhibition activity (IC 50 of 82.54 µg/mL) than single (IC 50 of 731.15 µg/mL) or double-juice combinations (IC 50 of 245.72 and 117.67 µg/mL) [ 25 ].…”
Section: Resultsmentioning
confidence: 85%
“… Artemisia annua L Yes [ 99 ] Yes [ 164 ] No 9. Azadirachta indica A. Juss Yes [ 165 ] Yes [ 166 ] Yes [ 167 ] 10. Camellia sinensis (L.) Kuntze Yes [ 168 ] Yes [ 169 ] Yes [ 170 ] 11.…”
Section: Edible Plants Exhibiting Antiviral Property Against Rna Virumentioning
confidence: 99%
“…To obtain protein hydrolysates from cocoa pod husk, enzymatic hydrolysis was performed using trypsin, pepsin, and alcalase. Hydrolysis was carried out using the optimal conditions for each enzyme as described by Arise et al 28 The enzyme was added to the protein solution at a ratio of 1 to 100 weight by weight. The optimal conditions were maintained, and the mixture continuously stirred for 4 hours.…”
Section: Enzymatic Hydrolysis Of Cocoa Pod Husk Proteinmentioning
confidence: 99%